2015
DOI: 10.1111/jomf.12265
|View full text |Cite
|
Sign up to set email alerts
|

Spillover in the Home: The Effects of Family Conflict on Parents' Behavior

Abstract: Spillover in the Home: The Effects of Family Conflict on Parents' BehaviorConflict with a spouse or child may generate spillover, defined as short-term affective changes in parents that affect their behavior with other family members. In a diverse sample of 86 parents, this 56-day diary study examined daily bidirectional spillover between conflict in the marital or parent-child dyad and parents' irritable, frictional behavior with their child or spouse, respectively. Tests of daily associations between conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 33 publications
5
80
3
Order By: Relevance
“…Mothers’ reports were used to assess fathers’ coparenting behavior, whereas fathers’ reports were used to assess mothers’ coparenting behavior. This approach has been used previously to guard against shared reporter variance (Sears, Repetti, Reynolds, Robles, & Krull, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Mothers’ reports were used to assess fathers’ coparenting behavior, whereas fathers’ reports were used to assess mothers’ coparenting behavior. This approach has been used previously to guard against shared reporter variance (Sears, Repetti, Reynolds, Robles, & Krull, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…For example, although cross-sectional and longitudinal studies have established associations between the extent and nature of marital and parent-child conflict (Erel & Burman, 1995), IRM designs have provided insights into the daily dynamics that give rise to these correlations. Daily diary reports indicate that the likelihood of hostile parenting behavior and parent-child conflict rise on days when spouses engage in conflict with each other (Erel & Burman, 1995;Sears, Repetti, Reynolds, Robles, & Krull, 2014). Almeida, Wethington, and Chandler (1999) found that marital tension on one day increased the likelihood of parent-child tension the next day by 41%-60% and that parent-child conflict raised the likelihood of same-day marital conflict.…”
Section: Short-term Social Emotional and Biological Processes That mentioning
confidence: 99%
“…These studies have then used the aggregate data to predict same-day associations (cross-sectionally) or next-day associations. In terms of same-day associations, Sears et al (2016) found that individuals who experienced marital conflict events on a particular day were more likely to display frictional parenting behavior towards their child (e.g., nagging, yelling) that same day. Findings were bidirectional.…”
mentioning
confidence: 99%
“…Findings were bidirectional. In other words, individuals who experienced parent-child conflict on a particular day were also more likely to display frictional marital behaviors that same day (Sears et al, 2016). Kouros et al (2014) found a similar positive association between individuals’ daily report of their marital quality and their report of their parent-child relationship quality that same day.…”
mentioning
confidence: 99%